Synthesis and microwave dielectric properties of Bi2Ge3O9 ceramics for application as advanced ceramic substrate - Ma, Xing-Hua; Kweon, Sang-Hyo; Nahm, Sahn; Kang, Chong-Yun; Yoon, Seok-Jin; Kim, Young-Sik (ELSEVIER SCI LTD, 2017)
During the synthesis of Bi2Ge3O9 ceramics using Bi2O3 + 3 GeO2 powders, the Bi4Ge3O12 phase was formed at low temperature (<= 800 degrees C). Bi4Ge3O12 preferentially adopted GeO2-excess phase, and this phase was consistently present in the sintered Bi2Ge3O9 ceramic as a secondary phase. Therefore, Bi4Ge3O12 powder was first calcined and subsequently reacted with GeO2 powder to obtain the pure Bi2Ge3O9 ceramic through the following reaction: 1/2B(4)Ge(3)O(12) + 3/2GeO(2) -> Bi2Ge3O9. Formation of the Bi2Ge3O9 phase was initiated at temperature of 850 degrees C. The pure Bi2Ge3O9 ceramic sintered at 875 degrees C for 8 h had a dense microstructure with an average grain size of 2.7 mu m. Furthermore, the pure Bi2Ge3O9 ceramic exhibited promising microwave dielectric properties for the advanced ceramic substrate: epsilon(r) = 9.7, Qxf = 48,573 GHz and tau(f) = -29.5 ppm/degrees C. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: CHEMICAL COMPATIBILITY; LTCC APPLICATIONS; LUMINESCENCE; BI4GE3O12; CRYSTALS; MN